Greater early and mid-pregnancy gestational weight gain are associated with increased risk of gestational diabetes mellitus: A prospective cohort study. (December 2017) - Zhong, Chunrong; Li, Xiating; Chen, Renjuan; Zhou, Xuezhen; Liu, Chaoqun; Wu, Jiangyue; Xu, Shangzhi; Wang, Weiye; Xiao, Mei; Xiong, Guoping; Wang, Jing; Yang, Xuefeng; et al.
Summary: Background & aims: Gestational diabetes mellitus is associated with adverse short- and long-term consequences for both the mother and the offspring. To examine the relationship between the rates of gestational weight gain (RGWG) during early and mid-pregnancy and the risk of gestational diabetes mellitus (GDM). Methods: 2090 singleton pregnant women from the Tongji Maternal and Child Health Cohort (TMCHC) without overt diabetes before pregnancy were analyzed in our study. Gestational weight were measured regularly in every antenatal visit. Gestational diabetes mellitus was assessed with the 75-g, 2-h oral glucose tolerance test at 24–28 weeks of gestation. Multivariable logistic regression was performed to estimate effect of RGWG on GDM. Results: A total of 8.3% (n = 173) of pregnant women were diagnosed with GDM. Women with elevated rate of gestational weight gain prior to glucose screening test (RGWG-PG) increased the risk of GDM (adjusted p -trend = 0.004; odds ratios (OR) 1.64, 95% confidence intervals (CI) 1.01–2.68 and OR 2.30, 95% CI 1.44–3.66 for 0.297–0.384 kg/wk and 0.385 kg/wk or more vs. 0.213 kg/wk or less, respectively). Women with greater rate of gestational weight gain in the first trimester (RGWG-F) increased the risk of GDM (adjusted p -trend = 0.048; OR 1.83, 95% CI 1.14–2.94 and OR 1.76, 95% CI 1.10–2.83 for 0.086–0.200 kg/wk and 0.201 kg/wk or more vs. −0.025 kg/wk or less, respectively). The rate of gestational weight gain in the second trimester (RGWG-S) was significantly associated with GDM only among women with RGWG-F more than 0.086 kg/wk (adjusted p -trend = 0.035; OR 2.04, 95% CI 1.16–3.59 for 0.658 kg/wk or more vs. 0.418 kg/wk or less). Conclusions: Greater early pregnancy weight gain are associated with increased risk of GDM. Elevated weight gain in mid-pregnancy increased the risk of GDM only among pregnant women with greater weight gain in the first trimester.